Ultrasound-Assisted Extraction, LC-MS/MS Analysis, Anticholinesterase, and Antioxidant Activities of Valuable Natural Metabolites from Astragalus armatus Willd.: In Silico Molecular Docking and In Vitro Enzymatic Studies - Sabrina Lekmine; Samira Bendjedid; Ouided Benslama; Antonio Ignacio Martín-García; Samira Boussekine; Kenza Kadi; Salah Akkal; Gema Nieto; Rokayya Sami; Amina A. M. Al-Mushhin; Morooj M. Baakdah; Abeer M. Aljaadi; et al. (MDPI AG, 2022)
The Astragalus armatus Willd. plant's phenolic constituent extraction and identification were optimized using the ultrasound-assisted extraction (UAE) method and the LC-MS/MS analysis, respectively. Additionally, cupric reducing antioxidant capacity (CUPRAC), beta carotene, reducing power, DMSO alcalin, silver nanoparticle (SNP)-based method, phenanthroline, and hydroxyl radical tests were utilized to assess the extract's antioxidant capacity, while the neuroprotective effect was examined in vitro against acetylcholinesterase enzyme. This study accurately estimated the chemical bonding between the identified phenolic molecules derived from LC-MS/MS and the AChE. The extract was found to contain sixteen phenolic substances, and rosmarinic, protocatechuic, and chlorogenic acids, as well as 4-hydroxybenzoic, hyperoside, and hesperidin, were the most abundant substances in the extract. In all antioxidant experiments, the plant extract demonstrated strong antioxidant activity and a significant inhibitory impact against AChE (40.25 ± 1.41 μg/mL). According to molecular docking affinity to the enzyme AChE, the top-five molecules were found to be luteolin, quercetin, naringenin, rosmarinic acid, and kaempferol. Furthermore, these tested polyphenols satisfy the essential requirements for drug-like characteristics and Lipinski's rule of five. These results highlight the significance of the A. armatus plant in cosmetics, as food additives, and in the pharmaceutical industry due to its rosmarinic and chlorogenic acid content.